Evidence for discrete modes of YAP1 signaling via mRNA splice isoforms in development and diseases - Vrbský, Jan; Vinarský, Vladimir; Perestrelo, Ana Rubina; De La Cruz, Jorge Oliver; Martino, Fabiana; Pompeiano, Antonio; Izzi, Valerio; Hlinomaz, Ota; Rotrekl, Vladimir; Sudol, Marius; Pagliari, Stefania; Forte, Giancarlo (Genomics, 2021)
Yes-associated protein 1 (YAP1) is a transcriptional co-activator downstream of Hippo pathway. The pathway exerts crucial roles in organogenesis and its dysregulation is associated with the spreading of different cancer types. YAP1 gene encodes for multiple protein isoforms, whose specific functions are not well defined. We demonstrate the splicing of isoform-specific mRNAs is controlled in a stage- and tissue-specific fashion. We designed expression vectors encoding for the most-represented isoforms of YAP1 with either one or two WW domains and studied their specific signaling activities in YAP1 knock-out cell lines. YAP1 isoforms display both common and unique functions and activate distinct transcriptional programs, as the result of their unique protein interactomes. By generating TEAD-based transcriptional reporter cell lines, we demonstrate individual YAP1 isoforms display unique effects on cell proliferation and differentiation. Finally, we illustrate the complexity of the regulation of Hippo-YAP1 effector in physiological and in pathological conditions of the heart.
Keywords: Alternative splicing; Tissue-specific expression; RNA, Messenger; Protein Isoforms; YAP-Signaling Proteins; protein - isoformy; Cell Cycle Proteins; signální proteiny YAP; RNA Isoforms; proteiny buněčného cyklu; Cardiac differentiation; messenger RNA; YAP1 isoforms; izoformy RNA